Vector competence of Aedes aegypti, Culex tarsalis, and Culex quinquefasciatus from California for Zika virus. - Bradley J Main; Jay Nicholson; Olivia C Winokur; Cody Steiner; Kasen K Riemersma; Jackson Stuart; Ryan Takeshita; Michelle Krasnec; Christopher M Barker; Lark L Coffey (PLoS Neglected Tropical Diseases, 2018)
Zika virus (ZIKV) has emerged since 2013 as a significant global human health threat following outbreaks in the Pacific Islands and rapid spread throughout South and Central America. Severe congenital and neurological sequelae have been linked to ZIKV infections. Assessing the ability of common mosquito species to transmit ZIKV and characterizing variation in mosquito transmission of different ZIKV strains is important for estimating regional outbreak potential and for prioritizing local mosquito control strategies for Aedes and Culex species. In this study, we evaluated the laboratory vector competence of Aedes aegypti, Culex quinquefasciatus, and Culex tarsalis that originated in areas of California where ZIKV cases in travelers since 2015 were frequent. We compared infection, dissemination, and transmission rates by measuring ZIKV RNA levels in cohorts of mosquitoes that ingested blood meals from type I interferon-deficient mice infected with either a Puerto Rican ZIKV strain from 2015 (PR15), a Brazilian ZIKV strain from 2015 (BR15), or an ancestral Asian-lineage Malaysian ZIKV strain from 1966 (MA66). With PR15, Cx. quinquefasciatus was refractory to infection (0%, N = 42) and Cx. tarsalis was infected at 4% (N = 46). No ZIKV RNA was detected in saliva from either Culex species 14 or 21 days post feeding (dpf). In contrast, Ae. aegypti developed infection rates of 85% (PR15; N = 46), 90% (BR15; N = 20), and 81% (MA66; N = 85) 14 or 15 dpf. Although MA66-infected Ae. aegypti showed higher levels of ZIKV RNA in mosquito bodies and legs, transmission rates were not significantly different across virus strains (P = 0.13, Fisher's exact test). To confirm infectivity and measure the transmitted ZIKV dose, we enumerated infectious ZIKV in Ae. aegypti saliva using Vero cell plaque assays. The expectorated plaque forming units PFU varied by viral strain: MA66-infected expectorated 13±4 PFU (mean±SE, N = 13) compared to 29±6 PFU for PR15-infected (N = 13) and 35±8 PFU for BR15-infected (N = 6; ANOVA, df = 2, F = 3.8, P = 0.035). These laboratory vector competence results support an emerging consensus that Cx. tarsalis and Cx. quinquefasciatus are not vectors of ZIKV. These results also indicate that Ae. aegypti from California are efficient laboratory vectors of ancestral and contemporary Asian lineage ZIKV.